2007
DOI: 10.1017/s0263034607000249
|View full text |Cite
|
Sign up to set email alerts
|

Collimated attosecond GeV electron bunches from ionization of high-Z material by radially polarized ultra-relativistic laser pulses

Abstract: Three dimensional Particle-in-Cell (3D-PIC) simulations of electron acceleration in vacuum with radially polarized ultraintense laser beams have been performed. It is shown that single-cycle laser pulses efficiently accelerate a single attosecond electron bunch to GeV energies. When multi-cycle laser pulses are used, one has to employ ionization of high-Z materials to inject electrons in the accelerating phase at the laser pulse maximum. In this case, a train of highly collimated attosecond electron bunches wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 19 publications
2
79
0
Order By: Relevance
“…The ADK tunneling ionization model [23][24][25] is used to describe the release of the inner-shell electrons from the nitrogen ions. The inner shell nitrogen's electrons (N 5+ → N 6+ and N 6+ → N 7+ ) are produced via ionization close to the peak of the leading (henceforth referred to as the pump) pulse intensity and are injected and get trapped inside the plasma bubble [21,22].…”
Section: Pic Simulations Of Single-and Two-colormentioning
confidence: 99%
“…The ADK tunneling ionization model [23][24][25] is used to describe the release of the inner-shell electrons from the nitrogen ions. The inner shell nitrogen's electrons (N 5+ → N 6+ and N 6+ → N 7+ ) are produced via ionization close to the peak of the leading (henceforth referred to as the pump) pulse intensity and are injected and get trapped inside the plasma bubble [21,22].…”
Section: Pic Simulations Of Single-and Two-colormentioning
confidence: 99%
“…However, strong acceleration can take place at the center of RPLBs without the action of the transverse field components [16,17,63,64]. Direct longitudinal acceleration with RPLBs allows for matching the electrons with the longitudinal field oscillations and effectively offers the possibility of producing well collimated quasi-monoenergetic relativistic attosecond electron pulses [16,18,19].…”
Section: Direct Longitudinal Electron Acceleration With Radially Polamentioning
confidence: 99%
“…A target should thus be composed preferably of a material with deeply bound inner shells so that most electrons remain bound during the rise time of the laser pulse, but released near the peak [17,19,70,71]. In that situation, electrons experience an optimal acceleration from z 0 to ∼ ∞.…”
Section: Direct Longitudinal Electron Acceleration With Radially Polamentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the importance of polarization effects, Kado et al [72] have observed strongly collimated proton beam from Tantalum targets when irradiated with circularly polarized laser pulses. With the help of radially polarized ultra relativistic laser pulses, Karmakar and Pukhov [73] have shown that collimated attosecond GeV electron bunches can be produced by ionization of high-Z material. They also compared the results with the case of Gaussian laser pulses and found that the radially polarized laser pulses are superior both in the maximum energy gain and in the quality of the produced electron beams.…”
Section: Acceleration Using Lasersmentioning
confidence: 99%